The use of icebreakers and games for interactive online learning - Herman Felani (Communications in Humanities and Social Sciences, 2022)
The COVID-19 pandemic has been affecting the teaching-learning process in all levels of education, including in higher education. The implementation of online teaching-learning process has been inevitable in the effort to reduce the people to people contact and to prevent the spread of the virus. However, there have been complaints that the interaction quality during online class or meeting is lacking of warm and meaningful communication between the participants and the teachers. This research aims to implement and evaluate some ice breaking and games during online meetings to achieve an interactive learning with the good communication quality between participants of online classes. This qualitative research used the approach of action research. The results indicated that the implementation of ice breaking and improvement of interaction has been positively perceived by the participants. Thus, using proper ice breaking and games during online meetings is suggested.